2016
DOI: 10.1371/journal.pone.0162878
|View full text |Cite
|
Sign up to set email alerts
|

Neisserial Heparin Binding Antigen (NHBA) Contributes to the Adhesion of Neisseria meningitidis to Human Epithelial Cells

Abstract: Neisserial Heparin Binding Antigen (NHBA) is a surface-exposed lipoprotein ubiquitously expressed by Neisseria meningitidis strains and an antigen of the Bexsero® vaccine. NHBA binds heparin through a conserved Arg-rich region that is the target of two proteases, the meningococcal NalP and human lactoferrin (hLf). In this work, in vitro studies showed that recombinant NHBA protein was able to bind epithelial cells and mutations of the Arg-rich tract abrogated this binding. All N-terminal and C-terminal fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…The immunogenicity and stability of the recombinant antigens was optimized by generating protein-protein fusions of fHbp-GNA2091 and NHBA-GNA1030, which induce higher serum bactericidal activity titers than those induced by the individual antigens alone (2). fHbp, Neisserial adhesin A, and NHBA have been extensively characterized and shown to be involved in meningococcal virulence (6)(7)(8)(9)(10)(11). The accessory protein GNA1030 has recently been characterized as a Neisseria ubiquinone binding protein (NUbp) (12).…”
mentioning
confidence: 99%
“…The immunogenicity and stability of the recombinant antigens was optimized by generating protein-protein fusions of fHbp-GNA2091 and NHBA-GNA1030, which induce higher serum bactericidal activity titers than those induced by the individual antigens alone (2). fHbp, Neisserial adhesin A, and NHBA have been extensively characterized and shown to be involved in meningococcal virulence (6)(7)(8)(9)(10)(11). The accessory protein GNA1030 has recently been characterized as a Neisseria ubiquinone binding protein (NUbp) (12).…”
mentioning
confidence: 99%
“…The important role of the NHBA Arg-rich region for host colonization and invasion was demonstrated previously for Heparin binding [7] and Neisseria meningitidis adhesion to Human Ephitelial Cells [16].…”
Section: Discussionmentioning
confidence: 85%
“…The role of NHBA in Neisseria meningiditis pathogenesis is still unclear. Previous studies have shown that NHBA is able to bind Heparin and GAGs on epithelial cells through the Arg-rich region [16] , supporting the hypothesis that NHBA can not only enhance bacterial survival in human serum, but can also play a crucial role during the adhesion step in Neisseria meninigitidis host colonization [15]. NHBA is cleaved by two specific proteases, NalP, a surface-exposed Neisseria serine protease, and human lactoferrin (hLf), present in several human biological fluids like serum, milk and saliva [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NHBA is a surface-exposed lipoprotein expressed by most meningococcal strains (Lucidarme et al, 2010;Tsang et al, 2015;Wang et al, 2011) and by other Neisseria species (Muzzi et al, 2013). Binding to heparin has been shown to improve the pathogen's survival in blood and to mediate adhesion to epithelial cells Vacca et al, 2016). NHBA peptide sequence can vary considerably, but cross-protection has been demonstrated across a variety of NHBA variants (Giuliani et al, 2010).…”
Section: Role and Contribution Of Fhbpmentioning
confidence: 99%